Approach to the Dramaturgy of Scenic Dance - Gómez de la Hoz, Iker (2025)
Introduction: This paper examines dramaturgy in stage dance, a term whose meaning is often diluted between choreographic composition and stage direction. Objective: Specifically, it aims to contextualize the terminology of choreographic dramaturgy in stage dance for the precision of its function. Methods: The research is based on a critical analysis through a bibliographical review of dramaturgy, contrasted with the observation of works from different dance territories. Results: Choreographic dramaturgy is presented as a functional entity that articulates meanings in choreographic writing, facilitates artistic intention, and considers the spectator’s engagement. Two approaches to its study are supported: the postulates of the science of complexity and the proposal of complementary bases to existing methods of choreographic analysis. Conclusions: The results of this work allow an approach to the interactions between contemplation and rituality in a contemporary artistic practice, presenting both as a way of knowledge capable of transforming the spectator.